GE_GERICHTE P/8740/2024 vom 6. Oktober 2025 - GE Cour de justice (2025)
RECEL;DISPOSITIONS PÉNALES DE LA LSTUP;LOI FÉDÉRALE SUR LES ÉTRANGERS ET L'INTÉGRATION;EXPULSION(DROIT PÉNAL);CONFISCATION(DROIT PÉNAL) | CP.160.ch1; LStup.19.al1.letc; LStup.19.al1.letd; LEI.119.al1; CP.14; CP.66a bis; CP.70.al1; CPP.442.al4